ENVIRONMENTAL MONITORING OF LVIV REGION AS A KEY TOOL FOR ENSURING SUSTAINABLE DEVELOPMENT AND MINIMIZING ENVIRONMENTAL RISKS - Іvankiv М.; Kachmar Н.; Datsko Т.; Dydiv А.; Balkovskyi В.; Horodyska І. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The article explores the vital role of environmental monitoring as a core element in achieving sustainable development, particularly within the context of Lviv region. It emphasizes that, in light of ongoing climate change and increasing human impact on the environment, the integration of digital technologies into the environmental monitoring system is essential. Given Lviv region's substantial industrial and transport potential, there are heightened environmental risks that pose threats to both environmental integrity and public health. Lviv region is positioned as a crucial player in fostering transparency, efficiency, and the soundness of management decisions. The analysis of the current state of the monitoring system in the region highlights critical aspects such as air quality, water resources, soil health, and waste management. The article argues for the necessity of incorporating innovative digital technologies, including GIS, satellite sensing, and Big Data, to enhance monitoring effectiveness. Furthermore, it stresses the importance of public participation and intersectoral collaboration in cultivating an environmental culture and promoting data transparency. The current state of the main environmental components in Lviv region was analyzed based on available data, namely the average annual concentration of fine particles PM2.5 in 2024 was 16,2±1,4 μg/m³, which was 8,6 % lower than in the IV quarter of 2023, but still exceeded the WHO recommendations (10 μg/m³). The ISA in Lviv for the period October 2024 – March 2025 was in the "high" category (9,58–9,68). The implementation of the IoT platform for monitoring the Western Buh and Stryi rivers allowed to reduce the response time to emergency discharges to 2 hours and reduce the volume of uncontrolled discharges by 18 %. The average annual concentrations of nitrates were 7,1±0,6 mg/l. Soil monitoring revealed an excess of lead concentrations in the industrial zones of Lviv and Sheptytskyi (42±5 mg/kg) by 31 % of the MPC (32 mg/kg), which made it possible to localize five priority areas for remediation. A decrease in total emissions from stationary sources to 58 thousand tons in 2023 was recorded (23.9 % less than in 2022), with emissions from the mining and extractive industries (48,3 %) and energy (31,6 %) sectors dominating. Special attention is paid to the implementation of innovative solutions at the national and local levels, in particular the creation of regional environmental monitoring centers and the installation of automated air quality observation points.